2015
DOI: 10.1111/njb.00588
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of Alyssum (Brassicaceae) inferred from molecular data

Abstract: Previous molecular phylogenetic studies have contributed greatly to our knowledge about the phylogenetic position and infra‐generic relationships of the genus Alyssum. Nevertheless, due to limited sampling and incongruences between the different markers used, the phylogenetic relationships within the genus are still unresolved. In this study, the phylogenetic relationships within Alyssum were studied using nrDNA ITS and plastid trnL‐F sequences from 171 accessions representing 112 species from five sections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
3
11
2
Order By: Relevance
“…This marker has been widely used in previous analyses of Alysseae and Alyssum s.l. for its useful phylogenetic signal (Warwick et al 2008;Cecchi et al 2010Cecchi et al , 2013Rešetnik et al 2013;Li et al 2015;Salmerón-Sánchez et al 2018;Melichárková et al 2019), while cpDNA sequences have usually only limited value for species delimitation and phylogenetic inference, as in the case of the related genus Alyssum (Zozomová-Lihová et al 2014;Španiel et al 2017). All sequences were retrieved from GenBank except for typical O. baldaccii from Crete, not previously investigated.…”
Section: Molecular Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This marker has been widely used in previous analyses of Alysseae and Alyssum s.l. for its useful phylogenetic signal (Warwick et al 2008;Cecchi et al 2010Cecchi et al , 2013Rešetnik et al 2013;Li et al 2015;Salmerón-Sánchez et al 2018;Melichárková et al 2019), while cpDNA sequences have usually only limited value for species delimitation and phylogenetic inference, as in the case of the related genus Alyssum (Zozomová-Lihová et al 2014;Španiel et al 2017). All sequences were retrieved from GenBank except for typical O. baldaccii from Crete, not previously investigated.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…W.D.J.Koch] due to a general external resemblance of the taxa in these two groups. However, morphological and molecular evidence clearly showed that Alyssum and Odontarrhena are monophyletic clades within the tribe Alysseae, deserving separate generic status (Warwick et al 2008;Cecchi et al 2010;Rešetnik et al 2013;Li et al 2015). According to the AlyBase database (Španiel et al 2015), Odontarrhena includes 87 species mainly distributed in the Euro-Mediterranean and Irano-Turanian regions.…”
Section: Introductionmentioning
confidence: 99%
“…W.D.J.Koch. However, recent phylogenetic research [27][28][29][30][31] has shown that Alyssum, as traditionally circumscribed, is not monophyletic. In particular, the species in sect.…”
Section: Introductionmentioning
confidence: 99%
“…Alyssum montanum L. has been used as a reference species in previous research, which concluded that it is nickel-intolerant and does not hyperaccumulate metals [47,48]; however, it should be noted that recent phylogenetic research suggests that Alyssum sensu stricto is not sister to Odontarrhena. Rather, the genus Clypeola L. is now considered part of the sister-group to Odontarrhena [29][30][31], so C. jonthlaspi L. was selected as a second reference species. Although hyperaccumulation may show a phylogenetic signal across lineages [28], it appears that no previous studies have characterized the responses of C. jonthlaspi to soil metals.…”
Section: Introductionmentioning
confidence: 99%
“…Still, we have recently published important contributions in these latter fields, e.g. Li et al () and Yousefi et al () on molecular phylogeny, Moradi et al () on spatial plant ecology, Torres‐García et al () on the evolutionary consequences of herbicide resistant plants, Paiva Farias et al () on tropical phenology and Tang et al () on molecular evolution in hybrids. We also know that many authors have found that the advantages of publishing with Nordic Journal of Botany, including a relatively fast review processes, rigorous editorial processing and editing of accepted manuscripts, advertising on social media, and Nordic Journal of Botany being society‐owned and run on a non‐profit basis, well compensate for the relatively low IF.…”
mentioning
confidence: 99%